The reputational effects of analysts' stock recommendations and credit ratings: evidence from operational risk announcements in the financial industry - Barakat, Ahmed; Ashby, Simon; Fenn, Paul (Elsevier, 2018)
This paper investigates whether more favorable stock recommendations and higher credit ratings serve as a reputational asset or reputational liability around reputation-damaging events. Analyzing the reputational effects of operational risk announcements incurred by financial institutions, we find that firms with a “Buy” stock recommendation or “Speculative Grade” credit rating are more likely to incur an equity-based reputational damage. In addition, firms with lower credit ratings incur a much more severe debt-based reputational damage. Moreover, credit ratings are more instrumental in mitigating the debt-based reputational damage caused by fraud incidents or incurred in non-banking activities. Furthermore, the misconduct of senior management could demolish the reputation of firms with less heterogeneous stock recommendations. Finally, credit ratings serve as an equity-based reputational asset in the short term but turn into an equity-based reputational liability in the long term. Overall, our analysis reveals that stock recommendations represent a reputational burden and credit ratings act as a reputational shield; however, the persistence and magnitude of such reputational effects are moderated by time and event characteristics.